Cone Beam Computed Tomography versus Digital Panoramic Radiography for Alveolar Bone Height Assessment: A Prospective Comparative Study (Medical Forum Monthly, 2023)
Objective: The main objective of the study is to find the comparison of cone beam computed tomography versus digital panoramic radiography for alveolar bone height assessment.Study Design: A prospective comparative studyPlace and Duration of Study: This study was conducted at the Farid Family Hospital, Rawalpindi, from June 2022 to December 2022.Materials and Methods: A total of 60 patients were included in the study, divided into two groups of 30 patients each. Patients was selected based on specific inclusion and exclusion criteria. Patients in Group A were undergone digital panoramic radiography using a standard panoramic X-ray machine. Group B patients were received CBCT scans using a state-of-the-art cone beam computed tomography machine.Results: Data were collected from 60 patients. Group A (digital panoramic radiography) and Group B (cone beam computed tomography - CBCT). The demographic characteristics of the patients, including age and gender distribution, were similar between the two groups, ensuring comparable baseline characteristics. The measurements of alveolar bone height were obtained from the radiographic images acquired for each patient in both groups. Two experienced dental radiologists independently analyzed the images, and the mean of their measurements was used to assess inter-observer reliability, which was found to be excellent with a high level of agreement between the two observers.Conclusion: It is concluded that CBCT provided significantly more accurate and reliable measurements compared to digital panoramic radiography. This finding was supported by high inter-observer reliability and a statistically significant difference in alveolar bone height measurements between the two imaging modalities.